Draft Annual Plan 1979-80 Statements Government of Pondicherry - Planning Commission (Planning Commission, 1979)
Draft Annual Plan 1979-80 Header of Development - Outlays and Expenditure Draft Annual Plan 1979 -80 Minor Heads of Development Schemewise Outlays and Expenditure D Ra Ft Annualplan-1979-80 - Selected - Targets and Achievements (Please Indicate Cumulative Totals For Each Year) Draft Annual Plan 1979-80 Centrally Sponsored Schemes - Outlays and Expenditure.
Government of Pondicherry Planning and Research Department